Comparison of One Dimensional Dynamic Analysis and Microtremor Measurement Results - Subaşi, Ozan; Haşal, Murat Emre; Özaslan, Bilal; İyisan, Recep; Yamanaka, Hiroaki; Chımoto, Kosuke (TMMOB İnşaat Mühendisleri Odası, 2019)
The deformation level of the surface soil layer due to strong ground motion has a considerable effect in soil-structure interaction problems. The shear strain values of the near surface soil deposits which are calculated by one dimensional (1D) seismic site response analyses can also be estimated by incorporating the results obtained from Horizontal-to-Vertical Spectral Ratio (HVSR) analysis of microtremor data and peak horizontal acceleration value of design ground motion. In this study, the seismic behaviour of soil layers at a site located in the vicinity of North Anatolian Fault were estimated by both 1D  equivalent linear seismic site response analyses under 14 different rock outcrop motion records and analyses of ground ambient noise-microtremor measurement data. A correlation is proposed for elastic and elasto-plastic deformation levels of surface soil layers in order to estimate the value of shear strain due to strong ground motion

Depremler sırasında zemin tabakalarında oluşan deformasyon seviyeleri, yapı-zemin etkileşiminde önemli rol oynamaktadır. Kuvvetli yer hareketi kayıtları kullanılarak yapılan bir boyutlu (1D) dinamik analizlerle yüzeye yakın zemin tabakaları için hesaplanan kayma şekil değiştirmeleri, küçük genlikli titreşimler-mikrotremor verisi analiz sonuçlarının tasarım yer hareketine ait en büyük yatay ivme değeriyle birlikte değerlendirilmesiyle de tahmin edilebilmektedir. Bu çalışmada, Kuzey Anadolu Fay Hattına yakın bir bölgede zemin tabakalarının deprem hareketi karşısındaki davranışı hem 14 farklı anakaya ivme kaydı kullanılarak yapılan 1D eşdeğer lineer dinamik analizlerle hem de mikrotremor ölçümlerinin analizi yardımıyla elde edilmiştir. Verilerin değerlendirilmesi sonucunda; kuvvetli yer hareketi sırasında yüzeye yakın zemin tabakalarında oluşacak kayma birim şekil değiştirmesinin belirlenebilmesi amacıyla, elastik ve elasto-plastik deformasyon seviyelerini kapsayan bir bağıntı önerilmiştir.
Bir Boyutlu Dinamik Analiz ve Mikrotremor Ölçüm Sonuçlarının Karşılaştırılması
Keywords: Civil Engineering; İnşaat Mühendisliği